z+3.27=8.36

Simple and best practice solution for z+3.27=8.36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z+3.27=8.36 equation:


Simplifying
z + 3.27 = 8.36

Reorder the terms:
3.27 + z = 8.36

Solving
3.27 + z = 8.36

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3.27' to each side of the equation.
3.27 + -3.27 + z = 8.36 + -3.27

Combine like terms: 3.27 + -3.27 = 0.00
0.00 + z = 8.36 + -3.27
z = 8.36 + -3.27

Combine like terms: 8.36 + -3.27 = 5.09
z = 5.09

Simplifying
z = 5.09

See similar equations:

| -5n+2=33 | | 4(-2w+1)+3=8(-1w-5)+47 | | 6c=2 | | 6h/2 | | 5x+418=7 | | 4w+3w-3w-2w-w=14 | | -10x+2=-38 | | 2x^2+10x-6x-30=4+8x+x^2 | | -180=1800-(-360) | | 6(x-5)=7[x-(3-x)] | | 13k-9k=4 | | 4/5y-8=2/5y-2 | | 9s-3s+s+2s-5s=8 | | 10r=2r+10 | | 2/3x-1/15=2/5 | | 0.5x+5=6 | | x-1+x+10=180 | | 6m+13=4m+3 | | 2k+k+45= | | X-7/4=2 | | X(3X+9)=264 | | -6(x+6)-5=2(x+7) | | 12w-8w-3w=12 | | 4g=144 | | -14w+7-20+12w= | | -42-7y=-105 | | -8y+11=83 | | U-6=-8 | | F/81=-3 | | m^3-6m^2+9m-3=0 | | -5y-4(4y-1)=3-1(3-y) | | 6x-5x=-105+98 |

Equations solver categories